Prevalence of postpartum depression and its associated risk factors: a cross-sectional study among Goan urban population, India - Narathattil, Akhila; Gauns, Suvidha; Mayekar, Shalaka; Fernandez, Ryan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Postpartum depression (PPD) is a common and serious mental health issue affecting women after childbirth. It manifests as low mood, decreased energy, and loss of interest in daily activities, significantly impacting the quality of life of mothers and their families. Understanding the prevalence and risk factors of PPD is crucial for developing targeted interventions, especially in populations where cultural, social, and economic conditions may influence mental health outcomes. Objectives were to estimate the prevalence of PPD in urban Goan women and identify the primary risk factors associated with PPD in this population. Methods: This cross-sectional study was conducted among postpartum women residing in urban areas of Goa. The participants were screened for PPD using EDPS standardized assessment tools. Sociodemographic, obstetric, and psychosocial variables were collected to examine potential risk factors associated with PPD. Data analyzed using SPSS and p value less than 0.05 taken as statistically significant. Results: The prevalence of PPD in the study sample was found to be 17.8%. Key risk factors identified included lack of social support, previous mental health history, socioeconomic challenges, and relationship difficulties. The study highlighted the significant influence of socio-economic and emotional support structures on the mental health of postpartum women. Conclusions: The findings underscore the need for targeted screening and intervention strategies for postpartum women, particularly in settings with similar cultural and socio-economic contexts. Healthcare providers should prioritize early identification and management of PPD to improve maternal mental health and overall well-being.